2003
DOI: 10.1523/jneurosci.23-15-06315.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Deficits in a Subclass of GABA Neurons in the Prefrontal Cortex of Subjects with Schizophrenia

Abstract: Markers of inhibitory neurotransmission are altered in the prefrontal cortex (PFC) of subjects with schizophrenia, and several lines of evidence suggest that these alterations may be most prominent in the subset of GABA-containing neurons that express the calcium-binding protein, parvalbumin (PV). To test this hypothesis, we evaluated the expression of mRNAs for PV, another calcium-binding protein, calretinin (CR), and glutamic acid decarboxylase (GAD67) in postmortem brain specimens from 15 pairs of subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

59
876
4
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 864 publications
(942 citation statements)
references
References 61 publications
59
876
4
3
Order By: Relevance
“…Activation of both prefrontal cortical interneurons and pyramidal cells is consistent with the actions of atypical APDs such as clozapine (Deutch and Duman, 1996). This is particularly interesting because the number and/or function of GABA interneurons in the PFC may be compromised in schizophrenia (Hashimoto et al, 2003;Benes et al, 2000;Lewis et al, 1999;Akbarian et al, 1995). Our data suggest that NT agonists activate PFC interneurons and could thereby compensate for a prefrontal cortical GABAergic deficit in schizophrenia.…”
Section: Discussionsupporting
confidence: 70%
“…Activation of both prefrontal cortical interneurons and pyramidal cells is consistent with the actions of atypical APDs such as clozapine (Deutch and Duman, 1996). This is particularly interesting because the number and/or function of GABA interneurons in the PFC may be compromised in schizophrenia (Hashimoto et al, 2003;Benes et al, 2000;Lewis et al, 1999;Akbarian et al, 1995). Our data suggest that NT agonists activate PFC interneurons and could thereby compensate for a prefrontal cortical GABAergic deficit in schizophrenia.…”
Section: Discussionsupporting
confidence: 70%
“…This is interesting, because growing evidence points to a deficient function of fast‐spiking GABAergic interneurones (Hashimoto et al . 2003, Gonzalez‐Burgos et al . 2010, Taylor & Tso 2014) as well as reduced capacity to generate gamma oscillations, as an important pathophysiological mechanism in schizophrenia (Uhlhaas & Singer 2010, Lewis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent unpublished observations also reveal a reduction in the density of CB-IR interneurons in dlPFC of subjects with schizophrenia (Rajkowska et al, 2002). Moreover, reductions in immunoreactivity for glutamic acid decarboxylase (GAD65) (the GABA synthesizing enzyme; Benes et al, 2000), mRNA for GAD (Akbarian et al, 1995;Hashimoto and Lewis, 2006;Hashimoto et al, 2003;Volk et al, 2000), and the GABA membrane transporter, GAT-1 (Pierri et al, 1999;Woo et al, 1998) have been observed in dlPFC and anterior cingulate cortex in manic-depressive disorder and schizophrenia. Whether similar reductions in GAD or GAT-1 mRNA and protein are present in our cohort of depressed subjects is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%